The Aspects of Human Rights Violation in Violent Actions in The Implementation of The Sea Alms Event in Beach Baru, Bantul District Yogyakarta - Kurniawan, Basuki; Purbosari, Nita Ryan (LP2M UIN KH.Achmad Siddiq Jember, 2023)
One day before the sea alms event held by coastal residents around Pantai Baru, Bantul Regency, a group of mobs carried out an act of violence that destroyed property (ubo rampe) for the event. The mass group considers that the marine charity event, which coastal residents routinely carry out, is an activity of shirk. Research in this journal is normative juridical (legal research), which focuses on studying the principles or norms in positive law, especially legal instruments in the field of Human Rights, both nationally and internationally. This type of research is carried out by examining formal legal regulations such as laws and literature containing theoretical concepts, which are then linked to the issues raised in the journal, namely aspects of human rights violations. The actions of a group of mobs that prevent the community from carrying out the sea alms tradition violate human rights. The government can try to protect the people's human rights in a preventive and repressive manner. This type of research is carried out by examining formal legal regulations such as laws and literature containing theoretical concepts, which are then linked to the issues raised in the journal, namely aspects of human rights violations. The actions of a group of mobs that prevent the community from carrying out the sea alms tradition violate human rights. The government can try to protect the people's human rights in a preventive and repressive manner. This type of research is carried out by examining formal legal regulations such as laws and literature containing theoretical concepts, which are then linked to the issues raised in the journal, namely aspects of human rights violations. The actions of a group of mobs that prevent the community from carrying out the sea alms tradition violate human rights. The government can try to protect the people's human rights in a preventive and repressive manner.